Bone Mineral Density in Patients with Atopic Dermatitis on Chronic Topical/Oral Corticosteroids - Dr. Kiran Chahal, Dr. Udit, Dr. Dhananjay Malage, Mr. Vishal Pol (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Atopic dermatitis (AD) is a chronic inflammatory skin disorder frequently managed withcorticosteroids. Long-term systemic corticosteroid therapy is associated with reduced bonemineral density (BMD), while the effects of chronic topical corticosteroids on bone health are less clearly defined